The influence of academic culture on quality management system ISO 9001 maintenance within Malaysian universities. Issue 3 (4th May 2017) - Basir, Siti Arni; Davies, John; Douglas, Jacqueline; Douglas, Alexander
ABSTRACT: This study investigates the influence of the elements of academic culture on quality management system ISO 9001 maintenance within Malaysian universities. There is a dearth of empirical studies on maintaining ISO 9001, particularly in the higher education context. From the literature review, academic culture was classified according to four elements – academic freedom, individualism, professionalism and collegiality. Two case studies were conducted within Malaysian universities that had been ISO 9001-certified for 5 years. At the time of this research, these two were the only universities that had certification for their entire organisation. (Most organisations gain certification for specific departments). The findings showed that academic freedom, individualism and collegiality had worked against ISO 9001 maintenance, while professionalism had influenced ISO 9001 maintenance both positively and negatively. The opposites of individualism (teamwork) and collegiality (managerialism) had supported ISO 9001 maintenance in one of the cases.